Alternative Paths to Public Financial Management and Public Sector Reform : Experiences from East Asia - So, Sokbunthoeun; Woolcock, Michael; April, Leah; Hughes, Caroline; Smithers, Nicola (Washington, DC: World Bank, 2018)
Reforming public-sector organizations--their structures, policies, processes and practices--is notoriously difficult, in rich and poor countries alike. Even in the most favorable of circumstances, the scale and complexity of the tasks to be undertaken are enormous, requiring levels of coordination and collaboration that may be without precedent for those involved. Entirely new skills may need to be acquired by tens of thousands of people. Compounding these logistical challenges is the pervasive reality that circumstances often are not favorable to large-scale reform. Whether a country is rich or poor, the choice is not whether, but how, to reform the public sector--how optimal design characteristics, robust political support, and enhanced organizational capability to implement and adapt will be forged over time.